Rationale for the Use of the Cluster Approach to the Formation of Localities in the Regional Economic System - Filippova, Maria K.; Mindlin, Yurii B.; Litvinenko, Inna L.; Kucherov, Aleksey V.; Shichiyakh, Rustem A.; Prokhorova, Victoria V. (International Review of Management and Marketing, 2016)
With the growing divergence in the level of formation of regional territorial localized sub-national economic space is a priority for the development of the cluster model of development management localities in the economy of the regions of the Russian Federation. Effective direction of solving this problem is the dominant national economic development of organizational and economic instruments of formation and development of clusters in the regional economic systems. Under these conditions, the fundamental importance is the interaction of government, business and institutional structures of civil society as the three key actors of the process clustering economy, as well as networking between the partner companies themselves. Their effective cooperation achieved in the framework of spatially localized economic systems - clusters, representing the totality of the territorial concentration of interconnected business interests of companies as well as government and public economic and social institutions necessary for the development of competitive advantages of clusters and regional economies as a whole. Keywords: cluster, approach, regional economy, locality JEL Classifications: C38; R12